Development finance : planning and control - Hicks, Ursula K. (Oxford : Clarendon Press, 1965)
The book is set out the basic principles of expenditure choice, monetary and fiscal measures, and budgetary control, as simply as possible, clothing them in a practical dress so that they can be of direct assistance to planners and administrators.
Includes index
osc 11/01/2019
Loans
Keywords: Fiscal policy; Development finance